THE EFFECTIVENESS OF GALERY WALK TECHNIQUE TOWARD GRAMMAR COMPETENCE OF ENGLISH DEPARTMENT STUDENTS OF UNHASY - Mukminatus Zuhriyah (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2020)
Almost all of the students who learn English assume that learning grammar of English is not so important. They often think that their English is already acceptable in every condition without good grammar. This assumption makes their care on how important grammar is for their English less. It causes their grammar competence becomes low. Besides, the lecturer’s way of teaching which is not interesting also gives contribution to this low competence. This pre-experimental research was done by implementing gallery walk technique which is believed as an interesting and challenging teaching technique in intermediate English grammar class. The objectives of this research were to know: (1) the students’ grammar competence before the implementation of gallery walk technique, (2) the students’ competence on grammar after being taught by using GWT and (3) the effectiveness of GWT towards students’ grammar competence. The population of this study was two classes of the third semester students of English language eduacation department of UNHASY in the academic year of 2019/2020. The sample was class B comprising of 19 students by using purposive sampling. The students’ average score of grammar before GWT was applied was 67. After GWT was implemented, their mean score of grammar became 73. Because the value of sig. (2-tailed) was lower than 0.05, it showed that the improvement of the average results of pretest and posttest was significantly different. Then, it came to the conclusion that GWT was effective for teaching grammar.